Changes in Brain Functional Network Connectivity in Adult Moyamoya Diseases - Zheng, Gaoxing; Lei, Yu; Li, Yuzhu; Zhang, Wei; Su, Jiabin; Qi, Xiaoying; Chen, Liang; Zhang, Xin; Gu, Yuxiang; Yu, Yuguo; Mao, Ying (Cognitive neurodynamics, 2021)
Moyamoya disease (MMD) is a cerebrovascular disease that is characterized by progressive stenosis or occlusion of the internal carotid arteries and its main branches, which leads to the formation of abnormal small collateral vessels. However, little is known about how these special vascular structures affect cortical network connectivity and brain function. By applying EEG analysis and graphic network analyses undergoing EEG recording of subjects with eyes-closed (EC) and eyes-open (EO) resting states, and working memory (WM) tasks, we examined the brain network features of hemorrhagic (H MMD ) and ischemic MMD (I MMD ) brains. For the first time, we observed that I MMD had the much lower alpha-blocking rate during EO state than healthy controls while H MMD exhibited the relatively low EEG activity rate across all the behavior states. Further, I MMD showed strong network connections in the alpha-wave band in frontal and parietal regions during EO and WM states. EEG frequency and network topological maps during both resting and WM states indicated that the left frontal lobe and left parietal lobe in H MMD patients and the right parietal lobe and temporal lobe in I MMD patients have clear differences compared with controls, which provides a new insight to understand distinct electrophysiological features of MMD. However, due to the small sample size of recruited patient subjects, the result conclusion may be limited.